The Harmonization of Eco-efficiency Standards: An Analysis on the Energy Enterprises of the G7 Group and the Emerging E7 Countries - Bulgakov, Andrey; Krikunov, Arseniy (International Journal of Energy Economics and Policy, 2020)
Attempts are being made to harmonize the many standards of business practice that exist outside of financial reporting, but they are limited either to a single industry or to the views of individual researchers. In this article we have harmonized international standards of eco-efficiency, compiled on the basis of multi-stakeholder approach and tested the set of indicators developed for the energy companies of the Group of Seven (G7) and the Emerging Seven (E7). We analyzed the non-financial reports of 56 companies from the GRI Database for the period 2015-2016 and plotted the decoupling of value added and environmental pollution. The study found that G7 energy companies do not adhere to the concept of sustainable development, while for E7 companies there is an absolute decoupling except for greenhouse gas emissions. We come to conclusion that socially responsible companies are able to gain competitive advantages in the framework of sustainable development, provided the transparency of business. Keywords: standards harmonization, eco-efficiency, sustainable development, decoupling JEL Classifications: O13, Q01, Q52, Q56 DOI: https://doi.org/10.32479/ijeep.9065